ANALISIS RESPON SISWA TERHADAP PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN KEARIFAN LOKAL PADA MATERI GETARAN DAN GELOMBANG - Taqwilawaty, Indah; Azizahwati, Azizahwati; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: this study aims to describe student responses in the application of the PjBL model assisted by local wisdom on vibration and wave materials. The research conducted is descriptive research. The subjects in this study were 31 students of grade VIII.1 MTs N 3 Rokan Hulu for the 2022/2023 academic year. The data collection technique used was a student response questionnaire. This student response questionnaire was given to students after the application of the PjBL model assisted by local wisdom ended. The results of the questionnaire of student responses to the application of the PjBL model assisted by local wisdom can be seen in each indicator. The first indicator, namely the learning of the project based learning (PjBL) model assisted by local wisdom, was fun and increased student creativity, obtaining 91.12% results in the very good category. The second indicator, namely the learning of the project based learning (PjBL) model assisted by local wisdom utilizing existing natural resources, obtained 89.78% results in the very good category. The third indicator, namely the project based learning (PjBL) model, is a new learning for students, obtaining 91.93% results in the very good category. The fourth indicator, namely project based learning (PjBL) model assisted by local wisdom, should be carried out in groups, obtaining 89.69% results in the very good category. The fifth indicator, namely the learning model of project based learning (PjBL) assisted by local wisdom in accordance with the 2013 curriculum (scientific), obtained 95.69% results in the very good category. The average result of the overall student response questionnaire indicator was 91.66% with a very good category. This indicates that the application of the PjBL model assisted by local wisdom on vibration and wave material received a very good response from the students.Keywords: student response, project based learning model assisted by local wisdom.